1973
DOI: 10.1021/ic50123a042
|View full text |Cite
|
Sign up to set email alerts
|

Base adducts of .beta.-ketoenolates. VI. Single-crystal electron paramagnetic resonance and optical studies of copper(II)-doped cis-bis(hexafluoroacetylacetonato)bis(pyridine)zinc(II), Cu-Zn(F6acac)2(py)2

Abstract: Registry No. Zn(F6acac)2(py)2,38402-93-6; Cu(F6acac)2 (py)2,38496-50-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Our first effort with group 11 chemistry was developed with β-ketoenolate complexes of Cu(II). The JT behavior of six-coordinate Cu(II) and then Cr(II) and Mn(III) complexes was a focus of our work for a number of years and involved the studies of some gifted people. Optical powder reflectance, single-crystal polarized electronic, and electron paramagnetic resonance spectroscopic studies were important, and the EPR spectra showed that JT distortion barriers could be very small, even in the solid state. A liquid crystal technique we developed later was applied by Hoffman to studies of inorganic and biological materials.…”
mentioning
confidence: 99%
“…Our first effort with group 11 chemistry was developed with β-ketoenolate complexes of Cu(II). The JT behavior of six-coordinate Cu(II) and then Cr(II) and Mn(III) complexes was a focus of our work for a number of years and involved the studies of some gifted people. Optical powder reflectance, single-crystal polarized electronic, and electron paramagnetic resonance spectroscopic studies were important, and the EPR spectra showed that JT distortion barriers could be very small, even in the solid state. A liquid crystal technique we developed later was applied by Hoffman to studies of inorganic and biological materials.…”
mentioning
confidence: 99%